EFFECT OF HOT ROLLING AND SOLUTION TREATMENT ON THE MICROSTRUCTURE AND MECHANICAL PROPERTIES OF FE-MN-SI-CR-NI SHAPE MEMORY ALLOY - Rohmah, Miftakhur -; Sendouw, Emmanoela Carissa; Tanjung, Rifqi Aulia; Utama, Dedi Pria; Mabruri, Efendi (Metalurgi, 2023)
Fe-14Mn-4Si-8Ni-11Cr SMA (shape memory alloy) was designed as a smart material because of its specific properties, which can memorize the original shape, so it has the potential to dampen vibration in seismic structures. Memory effect is triggered by SIM (stress-induced martensitic) transformation from γ-austenite to ε-martensite (hexagonal close-packed / HCP) structure, and it is recovered by heating after unloading. This study investigated the effect of hot rolling and solution treatment on the microstructure and its relationship with hardness and SME (shape memory effect) properties. The as cast of Fe-14Mn-4Si-8Ni-11Cr was hot rolled (900 and 1000 ℃) and solution treated (1000 and 1100 ℃). After the thermomechanical process, all microstructures consist of γ-FCC (face-centered cubic), the annealing twins, and a fine band of ε-martensite. The grain size of the γ-phase is 29.43, 41.96, 42.44, and 45.57 μm for samples B, C, D, and E, respectively. The higher the temperature of hot rolling and solution treatment applied, the larger the grain size obtained, indirectly reducing the hardness to 299.93 BHN and 286.52 BHN for samples D and E. The coarsened austenite grain, a lower number of annealing twins, and the pre-existing line band of ε-martensite are favorable to obtain the enormous recovery strain, up to 8.26% for sample E.